Studies in labour markets and industrial relations - Baldassarri, Mario (Palgrave Macmillan, 2003)
In the last twenty years, Italy has undergone significant changes in the functioning of the labor market and industrial relations. This makes it an excellent case study for evaluating labor market practices and possibilities for reform. This book brings together leading Italian and European scholars to trace the evolution of labor bargaining and industrial relations from both a theoretical and empirical perspective.